التركز المطري اليومي للموسم (2018/2019) في العراق - husayn, Ahmed; ناصر عبود الكناني, مالك (Journal of College of Education, 2022)
Rainfall concentration means the increase in the amount of rain fall in a specific area or the frequency of the number of rainfalls in an area without other neighboring areas spatially and temporally, and the concept of rain concentration is evident by the fluctuation and change in the intensity of rain in some areas, as well as the continuity of its fall during the rainy season, due to the changes occurring The strength, longevity and speed of arrival and formation of humid depressions, as well as the merging processes between depressions that have similar synoptic characteristics, which leads to an increase in the amounts of rain or the frequency of the number of rainfalls, monthly and seasonally.In order to know the characteristics of the rainy concentration of the season (2018/2019) in Iraq, the data of the meteorological stations included in the study showed a discrepancy between the time periods spatially and temporally, as the first period was characterized by recording the highest concentration in months (November, December, April, May) While the third period recorded the highest daily concentration in (October, January, February, March), while the second period did not record a high daily concentration during the rainy season (2018/2019) in Iraq. It is evident from the data of the quantitative concentration of rain in Iraq that the parts The northern and northeastern parts of Iraq were characterized by the abundance of rainfalls, which reflects the picture of the relative rain concentration for these regions, while the concentration begins to decline towards the southwest, registering the lowest values ​​of concentration during the rainy season.